Penggunaan Media Pembelajaran Berbasis Youtube Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas X di SMAN 3 Palembang - Lestari, Putrilestari; Kurnisar Kurnisar (FKIP, Universitas Palangka Raya, 2024)
One effort to improve student learning outcomes is to use good and appropriate learning media. The aim of this research is to determine the improvement in learning outcomes of class X students at SMA Negeri 3 Palembang through the use of YouTube-based learning media. The method used is classroom action research. The subjects of this research were 35 class X.5 students. The results of this research are that student learning outcomes in the learning process have increased, completeness of cycle 1 was 65.57% (24 students completed out of 35 students) with a percentage of student activity observations of 57.5% (Active) and teacher activity 87.2% (Very Good). Meanwhile in cycle 2 it increased to 90.43% (32 students completed out of 35 students. With an observation percentage of student activities of 77.5% (Active) and teacher activities of 92.8% (Very Good).